2015
DOI: 10.1002/rcs.1660
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y gastric bypass for super obese patients: what approach?

Abstract: Robotic RYGB can be performed safely in super obese patients with results that compare favorably with laparoscopic and open surgery. However, the robotic approach has a longer operative time. The exact role of robotics for super obese population needs to be clarified in larger and randomized trials before drawing definitive conclusions. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Despite the established safety of robotics in bariatric surgery, the main disadvantages continue to be increased operating time and cost [15][16][17], as well as increased readmissions, which indicates greater resource utilization [17]. In addition, the safety and benefit of robotics in SO patients has been poorly reported, although single-institutional data with small sample sizes have shown that robotic surgery is safe in this patient population, with comparable results to both open and laparoscopic approaches [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the established safety of robotics in bariatric surgery, the main disadvantages continue to be increased operating time and cost [15][16][17], as well as increased readmissions, which indicates greater resource utilization [17]. In addition, the safety and benefit of robotics in SO patients has been poorly reported, although single-institutional data with small sample sizes have shown that robotic surgery is safe in this patient population, with comparable results to both open and laparoscopic approaches [12].…”
Section: Discussionmentioning
confidence: 99%
“…One of the proposed benefits of robotic surgery in SO patients is decreased port site trauma due to decrease in abdominal wall torque with the remotecenter technology. In addition, robotic surgery filters out the surgeon's physiologic tremor and improves dexterity [11,12].…”
mentioning
confidence: 99%
“…Furthermore, MIS in these patients requires a high degree of expertise and technical skills. While MIS contributed to improved outcomes in bariatric surgery [11,12], less is known about current utilization trends and outcomes related to surgical technique for colorectal resections in super-obese patients.…”
mentioning
confidence: 99%